P.141 Primary intracranial melanoma complicated by cerebral venous sinus thrombosis: a case report and literature review. (June 2022) - Mann, JA; Yu, R; Tso, MK
Abstract : Background: Melanocytic tumors of the central nervous system (CNS) such as meningeal melanoma are exceedingly rare tumours derived from leptomeningeal melanocytes. Primary meningeal melanomas account for 0.1% of intracranial neoplasms with an incidence of approximately 0.5 per 10 million. Methods: We report the case of a previously healthy 47 year old male who presented with bilateral tonic-clonic seizure. Magnetic resonance imaging (MRI) demonstrated a homogenously-enhancing right temporal extra-axial lesion. The patient was stabilized on anti-epileptic medications and dexamethasone prior to proceeding with complete surgical resection of the lesion. Review of the current literature was conducted. Results: Macroscopically, the extra-axial lesion was heavily pigmented with invasion of the surrounding dura and skull. Histopathology revealed a poorly differentiated neoplasm with nuclear atypia and melanin-containing cells with strong SOX10 positivity and variable S100 positivity. Systemic workup was negative including absent ocular or cutaneous melanomas. Oncopanel was negative including absent BRAF mutation. He began checkpoint inhibitor therapy and subsequently developed cerebral venous sinus thrombosis (CVST) managed with anticoagulation. At 6 month follow-up, he was neurologically intact, working full-time, and had resumed immunotherapy. Conclusions: Primary intracranial melanoma is a rare tumour that can appear radiographically similar to meningioma. Surgical resection remains the mainstay of therapy for best long-term prognosis.